The tubulin polymerization inhibitor gambogenic acid induces myelodysplastic syndrome cell apoptosis through upregulation of Fas expression mediated by the NF-κB signaling pathway - Cheng Zhong; Shijun Wang; Lei Xia; Xiaoman Yang; Liguang Fang; Xianyi Zhang; Mengyue Wang; Haijun Zhao; Guanghui Wang; Jinglong Wu; Ruijian Guo; Ming Zhong; et al. (Cancer Biology & Therapy)
The development of an effective treatment for myelodysplastic syndrome (MDS) is needed due to the insufficient efficacy of current therapies. Gambogenic acid (GNA) is a xanthone constituent of gamboge, a resin secreted by Garcinia hanburyi Hook. f. GNA exhibits antitumor and apoptosis-inducing activities against some cancer cells, but the mechanism is unknown. This study aimed to validate the anti-proliferative and apoptosis-inducing effects of GNA on MDS cells and to elucidate the mechanisms underlying those activities. Apoptosis, proliferation and cell cycle of MDS-L cells were assessed by the caspase 3/7 assay, cell counting and flow cytometry, respectively. The levels of apoptotic, tubulin, NF-κB pathways, and Fas proteins were determined by Western blotting. CRISPR/Cas9 knockout (KO) plasmids were used to generate KO cells of p65 and Fas. MDS cell growth in a xenograft model was evaluated by the AkaBLI system. GNA induced MDS cell apoptosis, accompanied by a reduction in the anti-apoptotic protein MCL-1 expression, and inhibited their growth in vitro and in vivo. GNA combined with the MCL-1 inhibitor MIK665 potently suppressed the proliferation of MDS cells. GNA interfered with tubulin polymerization, resulting in G2/M arrest. GNA induced NF-κB activation and upregulation of Fas, the latter of which was inhibited by p65 KO. GNA-induced apoptosis was attenuated in either p65 KO or Fas KO cells. These results demonstrate that GNA inhibited tubulin polymerization and induced apoptosis of MDS cells through upregulation of Fas expression mediated by the NF-κB signaling pathway, suggesting a chemotherapeutic strategy for MDS by microtubule dynamics disruption.